2021
DOI: 10.1063/5.0042885
|View full text |Cite
|
Sign up to set email alerts
|

On the pulsed–pulseless mode transition of negative DC corona in atmospheric nitrogen

Abstract: Pulsed mode as a common phenomenon appears in many kinds of DC corona discharge, whose characteristics can be affected by some specific factors. In this paper, an important research field of pulsed mode, pulsed–pulseless mode transition, is investigated in needle–plate electrodes in nitrogen at atmospheric pressure, and we discuss the effect of external circuit, gas temperature, and associative ionization on mode transition by experiment and simulation. The external circuit coupling with plasma can make the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In another approach, a pin-to-plate corona discharge was used to process the guaiacol feed (Figure b). In this case, the gas-phase interactions mainly occurred at the plasma–liquid interface at temperatures above 700 K . According to the above analysis of the data presented in Figure c,d, the reaction temperature in the discharge zone determines whether the aromatic ring is hydrogenated or cracked.…”
Section: Resultsmentioning
confidence: 87%
“…In another approach, a pin-to-plate corona discharge was used to process the guaiacol feed (Figure b). In this case, the gas-phase interactions mainly occurred at the plasma–liquid interface at temperatures above 700 K . According to the above analysis of the data presented in Figure c,d, the reaction temperature in the discharge zone determines whether the aromatic ring is hydrogenated or cracked.…”
Section: Resultsmentioning
confidence: 87%
“…It is thought that a transient ion sheath consisting of positive ions forms during the temporal discharge, which has an effect on pulse formation. Sun et al [19,20] compared the current pulses in nitrogen and air and found that the pulse rising edge is very similar for pulses in these two gases. They also found that the electronegativity of the working gas affects the pulsed-pulseless mode transition.…”
Section: Introductionmentioning
confidence: 99%